Mangosteen vinegar from Garcinia mangostana: quality improvement and antioxidant properties. Issue 12 (December 2022) - Suksamran, Nathamon; Anantawat, Visaka; Wattanaarsakit, Phanphen; Wei, Chen; Rahman, Md. Atiar; Majima, Hideyuki J.; Tangpong, Jitbanjong
Abstract: Mangosteen ( Garcinia mangostana Linn.) fruit is rich in phenolic compounds which function as antioxidants and play a role in anti-inflammation, anti-hyperlipidemia, and anti-diabetic nephropathy. To investigate mangosteen vinegar (MV) by steaming under high pressure, explore the effects of fermentation, antioxidant activity, and sensory evaluation acceptable using the 9 -point Hedonic scale. Steamed mangosteen was processed to produce 3 types of mangosteen vinegar: mangosteen rind vinegar (MRV), mangosteen flesh vinegar (MFV), and mangosteen rind plus flesh vinegar (MRFV). All 3 kinds of mangosteen vinegar were obtaining >4% acetic acid and significantly higher total phenolic content (TPC), total flavonoid content (TFC), and free radical scavenging ABTS+ and DPPH- antioxidant activity than apple cider vinegar (ACV) ( p < 0. 05). The phenolic compounds analysis of mangosteen vinegar using HPLC were found Gallic acid, Catechin, Epicatechin, Vanillic acid, Trans-ferulic acid, Rutin, Gamma-mongostin, and Alpha-mangostin which showed almost higher than that found in ACV. Therefore, MVs produced from streamed mangosteen have higher antioxidants and were more acceptable using the 9-point Hedonic scale, a significantly higher statistical analysis of sensory evaluation than ACV, especially MFV. Taken together, steamed MVs should be further studied to prove the health benefits as a dietary supplement. Abstract : Mangosteen vinegar; Quality improvement; Antioxidant activity; Phenolic contents; Sensory evaluation.